398 Development of Swine Enteroids As a Model to Study Lawsonia Intracellularis Infection. (10th April 2018) - Trudeau, M; Resende, T P; Guo, Y; Urriola, P E; Shurson, G C; Gebhart, C J; Saqui-Salces, M
Abstract: The bacterium, Lawsonia intracellularis, causes proliferative enteropathy in a variety of species, most notably pigs. The mechanism for intestinal epithelial cell expansion during a L. intracellularis infection is not well understood, and development of a suitable in vitro model is needed. Enteroids are 3-dimensional structures grown in vitro, and containing the differentiated cells of the small intestine. Consequently, our objective was to develop an enteroid infection model for L. intracellularis using enteroids. Because L. intracellularis is a slow-growing bacterium, in vitro models must provide normal cell proliferation for extended time (5-28 d). Although enteroid culture techniques are well established for mice, this species may not be the best model for L.intracellularis infection because the severity of lesions in mice are not as intense as observed in pigs. While L. intracellularis causes disease and reduced profitability in swine production, there is limited information on effective methods to culture swine enteroids. Thus, we first tested the feasibility of infecting mouse enteroids with the bacteria, and then proceeded to develop a protocol for swine enteroid culture to evaluate L. intracellularis infection in swine. Mouse enteroids were successfully infected with L. intracellularis by microinjecting the bacterial suspension into the lumen of the enteroids, which resulted in immunohistochemical localization of L. intracellularis in the enteroid. To develop swine enteroids, intestinal crypts were isolated from sections of jejunum collected from finishing pigs by dissociation using ethylenediaminetetraacetic acid. The crypt suspension was pelleted by centrifugation and re-suspended in culture medium. Isolated crypts were mixed with Matrigel, and plated in 24-well plates forming firm Matrigel beads. Enteroid medium was added to the wells once Matrigel solidified. Medium was changed every 2 d, and enteroids were passaged once a wk. At 10 d, enteroids had an average diameter of 106 μm with 3 enteroids per well. Enteroids survived for a maximum of 50 d, and longest survival was in broken pieces of Matrigel that had separated from the firm Matrigel beads. We then determined if suspended pieces of Matrigel would enhance swine enteroid development in a second experiment. In broken Matrigel, enteroids survived for 28 d. By 10 d, enteroids had an average size of 76.3 μm and there were 16 enteroids per well. This approach provided a 3-wk time period where enteroids were useful for pathogen infection experiments. This infection model may be useful in determining mechanisms of the pathogenesis of L. intracellularis and potential treatment options.